Assessing the Knowledge and Practices regarding eye care and complications of Diabetes among Diabetic Patients 18 years and older, attending a tertiary Diabetic Clinic in Kampala, Uganda - Hope, Mackline (Department of Public Health and Family Medicine, 2020)
Purpose